A sequence symmetry analysis of the interrelationships between statins, diabetes and skin infections - Ko, Humphrey H.T.; Lareu, Ricky; Dix, Brett; Hughes, Jeffery; Parsons, Richard (WILEY, 2019)
© 2019 The British Pharmacological Society